Unimolecular and collision dynamics of gas-phase ions - Poon, Clement (University of Ottawa (Canada), 2008)
This thesis describes the research work on two aspects of gas-phase ion reactions. In the first project, the unimolecular chemistry of a series of nitroalkane proton-bound pairs was investigated by mass spectrometry and theoretical calculations. In addition to a simple dissociation reaction in which the hydrogen bond is cleaved to form protonated and neutral nitroalkanes, the nitroalkane proton-bound pairs can also lose nitrous acid via an internal SN2 rearrangement and t-butanol via a nitro-nitrite isomerization. The dissociations of (CH3NO2)((CH3)3CNO2)H + and (CH3CH2NO2)((CH3) 3CNO2)H+ proton-bound pairs were studied by variational transition state theory. Delta(DeltaS ‡) and Delta(DeltaS) of the two dissociation channels are similar for the dissociations of (CH3NO2)((CH 3)3CNO2)H+ but deviation becomes larger in the case of (CH3CH2NO2)((CH 3)3CNO2)H+. One should therefore be cautious when assuming Delta(DeltaS‡ ) = Delta(DeltaS) in competitive dissociation reactions of proton-bound pairs. In the second part of the research work, keV N2+./He, N2+./Ar and CO2+./He collisions were investigated by emission spectroscopy. The results provide two pieces of evidence that support the curve-crossing mechanism for collisional activation. Firstly, the relative emission intensities of the molecular ions and the fragments are independent of the ion translational energy within the studied energy range and secondly, the difference in the N2+. B 2Sigmau+ → X 2Sigma g+ emission intensities from N2+./He and N2+./Ar collisions can be accounted for by the slope difference at the crossing points based on the Landau-Zener curve-crossing model. Although the investigation of the relative intensities within the A 2piu → X 2pig emission of CO2+. resembles the Franck-Condon picture at high collision energy, the Franck-Condon principle can also be applied to the curve-crossing model as it is purely based on the grounds of short transition time. Therefore, linking this principle immediately to vertical transitions for collisional excitation could be misleading.
Keywords: Chemistry, Physical.